Patient-Driven Findings of Genetic Associations for PANS and PANDAS - Robert Steve Horvath; Samuel Keating (Faculty of Medicine, Diponegoro University, 2021)
Background: There are presently very few genetic studies for PANS (Pediatric Acute-Onset Neuropsychiatric Syndrome) or PANDAS (Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections). More work in genetic associations for PANS and PANDAS (P/P) is needed to increase understanding of these debilitating childhood disorders that have a range of presentations.Objective: This work represents a novel approach that aims to determine genetic associations between P/P and other diseases, disorders and traits (hereafter referred to as phenotypes).Methods: Consumer genetic data (23andMe, AncestryDNA) for 155 patients with P/P were obtained from consenting parents over a period from 2018 to 2020. An analysis plan for this work was registered at Open Science Framework, additional genotypes imputed using Impute.me, and polygenic risk scores for 1,702 phenotypes calculated for each of the 155 P/P patients.Results: One-sample t-tests performed across the 155 individual risk scores revealed that P/P is statistically significantly associated with 21 different groups of Single Nucleotide Polymorphisms (SNPs) that are in turn associated with 21 phenotypes. Some of the 21 phenotypes (see Table 3) are previously known to be related to or associated with P/P: a group of SNPs associated with Tourette’s Syndrome, and another group associated with Autism Spectrum Disorder or Schizophrenia, and a third associated with “feeling nervous” yielded t-tests with p values of 1.2x10-5, 1.2x10-11 and 1.0x10-5 respectively for association with the P/P data. This validated our analysis methodology. Our analysis also revealed novel genetic associations such as between P/P and plasma anti-thyroglobulin levels (p=1.3x10-7), between P/P and triglycerides (p=5.6x10-6), and between P/P and Lewy body disease (p=7.8x10-6), inviting further investigation into the underlying etiology of P/P.Conclusion: P/P is associated with many phenotypes not previously recognized as being connected to P/P. Further work on these connections can lead to better understanding of P/P.